Female Education in Nigeria: A Key to Development in ESAN North East Local Government Area, Edo State, Nigeria - T. O., Ebhomienlen; V. O, Aitufe (International Journal of Educational Studies, 2018)
This essay portrays Female Education in Nigeria as a key to Development in Esan North East Local Government Area, Edo State. The need to break the barrier of sex discrimination at the crucial time that Nigeria needs all round development is more appealing. The female folks are supposed to be co – pilots of the wheel of progress. It is evident in Esan North East Local Government Area that the traditional view of women has not drastically changed. Most women are still into petty business, like trading, farming, menial fashion making, hair making and so on. The new wind of change that is blowing in some parts of Nigeria has not sufficiently reflected in the area of this study. This study therefore, aims at encouraging females themselves and their parents to change their past view on education and respond positively on female education campaign initiates. To achieve the objectives of this essay the researcher adopts the historical, analytical and phenomenological methodology. It discovers that the training of girls/ women will enhance the social, political and economic status of women themselves and the society at large and this will form the bedrock for holistic development.